Local buckling of S960 ultra-high strength steel welded I-sections subjected to combined compression and major-axis bending - Su, Andi (2022)
This paper presents an in-depth experimental and numerical investigation into the local buckling behaviour of S960 ultra-high strength steel welded I-sections under combined compression and bending moment about the major principal axis. Two I-sections (I-120 × 120 × 6 and I-150 × 75 × 6) were considered in the experimental investigation, and for each I-section, five eccentrically loaded stub column tests were conducted under different initial loading eccentricities. The experimental results were then adopted in a numerical investigation for validating finite element models, by means of which parametric studies were conducted to generate additional numerical data over a wide range of cross-section dimensions and initial loading eccentricities (i.e. loading combinations). The obtained experimental and numerical results were used to evaluate the applicability of the relevant design interaction curves, as set out in the European code, American specification and Australian standard, to S960 ultra-high strength steel welded I-sections under major-axis combined loading. The evaluation results revealed that (i) the European code results in safe but slightly conservative failure load predictions, (ii) both the American specification and Australian standard lead to relatively accurate failure load predictions and (iii) all the three design codes offer a good level of design consistency.